The Influence of Vocabulary Self-Collection Strategy on the Vocabulary Mastery - Intan Chrysti Olivia; Sri Yuliani; Dita Adawiyah (Universitas Pahlawan Tuanku Tambusai, 2022)
The objective of the study was to find out there was a significant influence of using vocabulary self-colection strategy on the vocabulary mastery of the Seventh Grade Students at SMP YKPP Pendopo. The method was pre-experimental. The population of this study was the seventh grade students of SMP YKPP Pendopo with totaling 105 students. The sample selected by using convenience method with the total 31 students. The data collected by mean of tests, namely pretest and posttest. The data analyzed by Matched t-test. The score of tobtained was 0.0083 1697 at the significant level p0.05 for two tailed and degree of freedom was 30, t table was 1.697. It indicated that the used of vocabulary self-collection strategy on the vocabulary mastery of the seventh grade students at SMP YKPP Pendopo was significant influence.